1998
DOI: 10.1038/bjc.1998.565
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the stathmin gene in a subset of human breast cancer

Abstract: Summary Stathmin is a highly conserved cytosolic phosphoprotein that destabilizes microtubules. Stathmin, which has been proposed as a relay protein integrating diverse cell signalling pathways, acts in vitro as a tubulin-sequestering protein, and its activity is dramatically reduced by phosphorylation. Interestingly, stathmin expression and phosphorylation are regulated during the control of cell growth and differentiation, and there is much evidence suggesting that in vivo stathmin plays a role in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 51 publications
6
83
0
Order By: Relevance
“…These results suggested that the expression of stathmin could contribute to cancer progression/prognosis, and that stathmin may have potential as a biomarker and a therapeutic target for OSCC. These results were in accordance with the high level of stathmin expression in many types of cancer, including leukemia and lymphoma, 65 prostate carcinoma, 66 ovarian carcinoma, 67 Wilms tumor, 68 breast carcinoma, 69 and adenoid cystic carcinoma of the salivary glands. 70 To identify potential biomarkers for laryngeal SCC, Sewell et al compared the protein profile of laryngeal cancer tissue with normal mucosal samples using 2D gel electrophoresis and MS. 44 The differentially expressed proteins were stratifin, S100 calcium-binding protein A9, p21-ARC, stathmin, and enolase.…”
Section: Tissue Biomarker Studiessupporting
confidence: 71%
“…These results suggested that the expression of stathmin could contribute to cancer progression/prognosis, and that stathmin may have potential as a biomarker and a therapeutic target for OSCC. These results were in accordance with the high level of stathmin expression in many types of cancer, including leukemia and lymphoma, 65 prostate carcinoma, 66 ovarian carcinoma, 67 Wilms tumor, 68 breast carcinoma, 69 and adenoid cystic carcinoma of the salivary glands. 70 To identify potential biomarkers for laryngeal SCC, Sewell et al compared the protein profile of laryngeal cancer tissue with normal mucosal samples using 2D gel electrophoresis and MS. 44 The differentially expressed proteins were stratifin, S100 calcium-binding protein A9, p21-ARC, stathmin, and enolase.…”
Section: Tissue Biomarker Studiessupporting
confidence: 71%
“…It is a critical regulator of microtubule dynamics during cell cycle progression and governs preferential microtubule growth around chromosomes during spindle assembly (48). Stathmin is expressed at elevated levels in various human tumors (49,50), and it is expressed at higher levels in proliferating cells as compared with non-proliferating cells (51). The Stathmin promoter contains three E2F-binding sites (47), and a recent study indicates that Stathmin levels are regulated by E2F (33).…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Stathmin is expressed at high levels in a wide variety of human malignancies. [56][57][58][59] We identified overexpression of stathmin in ACC tissue. Further, we detected stathmin protein expression in 2 cases with NSG, 10 cases of PA and 10 cases of ACC using immunohistochemistry (Fig.…”
Section: Figurementioning
confidence: 99%